Pharmacist-Physician Interprofessional Collaboration to Promote Early Detection of Cognitive Impairment: Increasing Diagnosis Rate - Ramos, Hernán; Pardo, Juan; Sánchez, Rafael; Puchades, Esteve; Pérez-Tur, Jordi; Navarro, Andrés; Moreno, Lucrecia (Frontiers in Pharmacology, 2021)
The increased pressure on primary care makes it important for other health care providers to collaborate with general practitioners in activities related to chronic disease care. Therefore, the objective  of the present project was  to develop a protocol of action that allows close pharmacist-physician collaboration to carry out a coordinated action for very early detection of cognitive impairment  (CI). A comparative study to promote early detection of CI was conducted in 19 pharmacies divided into two groups: one group with interprofessional collaboration (IPC) and one group without interprofessional collaboration (NonIPC). IPC was defined as an interactive procedure involving all  pharmacists, general practitioners and neurologists. A total of 281 subjects with subjective memory complaints were recruited. Three validated tests were used in the pharmacies to detect possible CI. Individuals with at least one cognitive test compatible with CI, were referred to primary care, and when appropriate, to the neurology service. Finally, we evaluated the differences in clinical and diagnostic follow-up in both groups after six months. The NonIPC study group included 38 subjects compatible with CI referred to primary care (27.54%). Ten were further referred to a neurology department (7.25%) and four of them (2.90%) obtained a confirmed clinical diagnosis of CI. In contrast, in the IPC group, 46 subjects (32.17%) showed results compatible with CI and were referred to primary care. Of these, 21 (14.68%) were subsequently referred to a neurology service, while the remaining 25 were followed up by primary care. Nineteen individuals out of those referred to a neurology service obtained a confirmed clinical diagnosis of CI (13.29%). The percentage of subjects in the NonIPC group referred to neurology and the percentage of subjects diagnosed with CI, was significantly lower in comparison to the IPC group (p-value = 0.0233; p-value = 0.0007, respectively). The creation of IPC teams involving pharmacists, general practitioners, and neurologists allow for increased detection of patients with CI and facilitates their clinical follow-up. This opens the possibility of diagnosis in patients in the very early stages of dementia, which can have positive implications to improve the prognosis and delay the evolution of the disease.